FOREIGN DIRECT INVESTMENT AND AGRICULTURAL SECTOR PERFORMANCE IN NIGERIA: A DISAGGREGATED APPROACH - AMALACHUKWU CHIJINDU ANANWUDE; CHARLES EMEKA NWOBIA; PAUL KENECHUKWU ONYEGIRI (Innovare Journal of Social Sciences, 2025)
The study examined the effect of foreign direct investment (FDI) on agricultural sector performance in Nigeria. The specific objective was to determine the extent to which FDI affects crop production, livestock, forestry, and fishery real output. This study utilized an ex-post facto research design. Secondary data were obtained from the Central Bank of Nigeria from 1986 to 2023. The time series data were analyzed using the Ordinary Least Squares regression technique. The findings revealed that FDI has a significant (0.0002 < 0.05) positive effect on crop production; a significant (0.0004 < 0.05) positive effect on livestock; a significant (0.0044 < 0.05) positive effect on forestry; and a significant (0.0010 < 0.05) positive effect on fishery real output in Nigeria. The study concludes that FDI is a panacea for agricultural sector performance in Nigeria. It will be an innovative approach if the Federal Ministry of Agriculture and Rural Development actively seeks and attracts more FDI by creating favorable policies and incentives for foreign investors to continue enhancing crop production in Nigeria. The Nigerian Investment Promotion Commission should collaborate with international agribusiness firms to introduce more advanced livestock farming technologies and practices to further boost livestock output.